2018
DOI: 10.1590/1806-9282.64.07.595
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer: Is grief a risk factor?

Abstract: SUMMARY Cancer is characterized by the disordered growth of cells that have high capacity of invasion to the tissues and organs. One of the types of tumour that has national incidence and high mortality is breast cancer. Studies show that in addition to hereditary factors, lifestyle and environmental factors, there are factors related to emotional distress (mourning), which interfere with the development of breast cancer. Thus, it is necessary to investigate if the experience of mourning can trigger the appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…As noted above, one underlying mechanism may be that both children with underlying cancer predisposition syndromes and their mothers may experience inferior outcomes as a result. However, the process of bereavement itself has also been linked to mortality and cancer incidence in broader populations 46–48 . Prolonged grief and attendant psychological symptoms are common among bereaved parents 49 .…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, one underlying mechanism may be that both children with underlying cancer predisposition syndromes and their mothers may experience inferior outcomes as a result. However, the process of bereavement itself has also been linked to mortality and cancer incidence in broader populations 46–48 . Prolonged grief and attendant psychological symptoms are common among bereaved parents 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer has become the most prevalent cancer worldwide and the first leading cause of cancer death in women [ 1 ]. The occurrence of breast cancer can be attributed to a variety of related risk factors, such as age, family history, alcohol consumption, and obesity [ 2 ], but the exact etiology of breast cancer remains undetermined, and the probability of cancer development, treatment effect, and survival still cannot be accurately predicted [ 3 ]. There are additional factors associated with the development of breast cancer waiting to be explored, one of which is the human microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common malignant tumor in women, accounting for 30% of female cancers in 2020 [ 1 ]. Several factors are known to affect women’s risk of breast cancer, including lifestyle, age, radiation exposure, obesity and so on [ 2 , 3 ]. Besides, recent studies have shown that the human microbiome, including gut microbiome, may be associated with the development of breast cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%